Penerapan Technology Acceptance Model (TAM) dalam Pengujian Model Penerimaan Aplikasi MasjidLink - Agus Mulyanto; Sumarsono Sumarsono; Thaqibul Fikri Niyartama; Annisa Khodista Syaka (Semesta Teknika, 2020)
MasjidLink is an Android-based application to provide news and information relating to mosques in the Yogyakarta Special Region. Behavioral aspects that influence tamir when using MasjidLink are need to measure, so that can define the level of acceptance. The TAM (Technology Acceptance Model) approach was used in this research to analyze factors of takmir acceptance towards MasjidLink. The measurement of acceptance  towards MasjidLink with TAM is expected to showing the actual perspective of tamir so can  helps the further developing of this applications. Testing research instruments through validity and reliability. All research instruments have a value of more than 0.5 so that it can be declared as valid instruments. TAM variable in this study has an alpha cronbatch value of more than 0.7, so that all of these research variables are said to be reliable. Perceived ease of use has a percentage value 72.68% which states that mosque takmir agrees with the ease of use of the MasjidLink application. Perception of usefulness has a percentage 72.11% which states that the mosque takmir agrees with the usefulness of the MasjidLink application. Acceptance of the application has a percentage value 71.31% which states that the mosque takmir agrees with the acceptance of the MasjidLink application. The results of descriptive statistical analysis on TAM have the smallest percentage of variables, there is the percentage of MosqueLink acceptance with the value is 71.31%. This can be used to enhance the development of MasjidLink by focusing on the acceptance of the MasjidLink application. MasjidLink is an Android-based application to provide news and information relating to mosques in the Special Region of Yogyakarta. Currently, MasjidLink is a new mosque information management application that was launched and started to implemented by several takmir mosques in the Special Region of Yogyakarta. Takmir's acceptance of the MasjidLink application is one of the factors that support the continued use of the application. The measurement of the mosque takmir acceptance on the MasjidLink application is done by the TAM (Technology Acceptance Model) method. This study aims to evaluate the application of MasjidLink application with the TAM method so that the perception of takmir and the factors that influence takmir in using the application can be known. The research method used is a quantitative method, which uses a questionnaire as a tool to collect data on 125 users of the MasjidLink application. The results showed acceptance of mosque takmir on MasjidLink application had a positive influence on 3 TAM variables, namely the perception of user convenience 72.68%, perceived usefulness of 72.11%, and technology acceptance 71.31%. This shows that the application developer can focus on improving the acceptance of the MasjidLink application variable because the variable percentage is smaller than other variables.